Avaliação de desempenho dos departamentos acadêmicos da UFSCar utilizando análise de envoltória de dados-AED. - Panepucci, Giovana Troya Marques (2003)
The need to access public or private institutions has long existed. Of our interest, is the measure of efficiency among different departments of a public university. Unlike most private universities; a public university does not focus on teaching, as it is only output. Together with this, public universities produce knowledge as a whole, in the form of research (with the development of new technologies) and extension activities. The diverse character of production demands mathematical methods to quantify efficiency, point out deficiencies related to specific output (or input) measures and provide targets. Data Envelopment Analysis (DEA) is proposed to access the efficiency of the departments of the Universidade Federal de São Carlos UFSCar . To apply DEA, many production indicators were generated from data available from the year 2001. A general efficiency classification of all thirteen departments of UFSCar in relation to seven measures of production in the fields of teaching, research and extension activities, and two measures of resources was obtained. In addition, individual classifications were obtained by considering a field at a time or considering related sets of departments belonging to a given center. The incompleteness of precise data was a limiting factor in this analysis, hampering, in some cases, the obtainment of a realistic image of efficiency. In this way, the results showed here, must be seem with caution, a must be used only as a reference on the understanding of the difficulties associated with the complex task of efficiency assessment and target establishment.